A high energy density additive material and its preparation method and application

By using organic solution system polymerization reaction during the synthesis of Li5FeO4, and adding repair substances and carbon source substances for repair after sintering, the problem of Li5FeO4 particle size and stability is solved, and high energy density and excellent electrical properties are achieved.

CN116354403BActive Publication Date: 2025-03-07GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310210642.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-07
Publication Date
2025-03-07
Estimated Expiration
2043-03-07

AI Technical Summary

Technical Problem

The existing Li5FeO4 synthesis method has problems such as large particles, irregular surface morphology, poor conductivity, unstable and prone to deterioration, resulting in insufficient energy density and stability in lithium-ion batteries.

Method used

By placing nano-scale iron salts in an organic solution system for polymerization, an organic polymer-coated precursor is formed and mixed with lithium source materials to sinter it to form a dense carbon shell to control the particle size and distribution; after sintering and pulverizing, repairing substances and carbon source materials are added for secondary sintering to repair damage on the particle surface.

Benefits of technology

The prepared Li5FeO4 particles have smaller particle sizes, more uniform distribution, significantly improved stability and electrical properties, and their capacitance reaches more than 640 mAH/g, which is better than materials prepared by conventional dry-mixed carbon sources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116354403B_ABST
    Figure CN116354403B_ABST
Patent Text Reader

Abstract

A method for preparing an additive material with high energy density comprises the following steps: S1: placing a nano-sized iron salt in an organic solution system, stirring and controlling the temperature to 30°C-50°C and the pH to 3-6, performing a polymerization reaction, aging and standing, solid-liquid separation, and drying to obtain an organic polymer-coated precursor; S2: mixing and stirring the organic polymer-coated precursor with a lithium source material, then sintering and crushing to obtain a semi-finished product; S3: mixing the semi-finished product with a repairing material and a carbon source material, and then sintering to obtain Li5FeO4 particles, i.e., a finished product of an additive material with high energy density. The electrical properties, stability, and specific capacity of the Li5FeO4 particles prepared by the present invention are significantly better than those prepared by conventional dry mixed carbon sources, and the capacitance can reach more than 640mAH / g, which is much higher than the capacitance of 540mAH / g of the Li5FeO4 granular material prepared by ordinary conventional dry mixed carbon sources. Moreover, the synthesis process of the method disclosed in the present invention is simple, the processing cost is low, and the efficiency is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery materials, and in particular relates to a high energy density additive material and a preparation method and application thereof. Background Art

[0002] At present, the requirements for energy density of lithium batteries are getting higher and higher. However, when lithium batteries are charged for the first time, lithium ions are lost due to the formation of SEI film, resulting in a certain degree of capacity loss. To improve this situation, some lithium-rich substances are usually added to the positive electrode material as additives.

[0003] Li 5 FeO 4 It has the advantages of high lithium content, low metal element cost, low charging voltage platform, and high theoretical capacity. It is an excellent positive electrode material additive. However, at present, Li 5 FeO 4 There are still some problems in the synthesis method, such as the synthesis of Li 5 FeO 4 Problems include large particles, irregular surface morphology, poor conductivity, instability, and easy deterioration. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a high energy density additive material and a preparation method and application thereof, aiming to prepare a high energy density Li-ion battery with small particle size, uniform particle size distribution, regular morphology and good stability. 5 FeO 4 Additives are used to prepare lithium-ion batteries with high energy density. The present invention specifically includes the following contents:

[0005] A method for preparing an additive material with high energy density comprises the following steps:

[0006] S1: placing an iron salt in an organic solution system, stirring and controlling the temperature of the organic solution system to 30°C-50°C and the pH to 3-6, performing a polymerization reaction, aging and standing after the reaction, and then performing solid-liquid separation and drying to obtain an organic polymer-coated precursor; the temperature of the organic solution system can be specifically 30°C, 32°C, 35°C, 40°C, 45°C, 50°C, etc., and the pH can be 3, 4, 4.5, 5, 5.5, 6, etc.; the iron salt is preferably a nano-grade iron salt;

[0007] S2: mixing and stirring the organic polymer-coated precursor and the lithium source material, and then sintering and crushing to obtain a semi-finished product;

[0008] S3: Mix the crushed semi-finished product with the repair material and the carbon source material, and then sinter them to obtain Li 5 FeO4 Pellets, i.e. finished products of additive materials with high energy density.

[0009] Specifically, in step S1, the particle size of the iron salt is 100nm-900nm, specifically 100nm, 200nm, 300nm, 500nm, 700nm, 800nm, 900nm, etc.; the organic solution system is a mixture of one or more of resorcinol, formaldehyde, pyrrole, thiophene, aniline, and butyl titanate.

[0010] Specifically, in step S1, the stirring speed is 100 rpm-400 rpm, and specifically can be 100 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, etc.

[0011] Specifically, in step S1, the aging standing time is 2h-5h, specifically 2h, 3h, 3.5h, 4h, 4.5h, 5h, etc.; the drying temperature is 70℃-150℃, specifically 70℃, 80℃, 90℃, 100℃, 120℃, 140℃, 150℃, etc.

[0012] Specifically, in step S2, the molar ratio of the iron element in the organic polymer-coated precursor to the lithium element in the lithium source material is 1.0:(4.8-5.8), and can be specifically 1.0:4.8, 1.0:5.0, 1.0:5.2, 1.0:5.4, 1.0:5.6, 1.0:5.8, etc.

[0013] Specifically, in step S2, the sintering temperature is 500℃-700℃, specifically 500℃, 550℃, 600℃, 650℃, 700℃, etc.; the sintering time is 8h-30h, specifically 8h, 10h, 12h, 18h, 20h, 25h, 28h, 30h, etc.; the Dv50 of the semi-finished product obtained after the crushing is 2μm-4μm, specifically 2μm, 2.4μm, 2.8μm, 3.2μm, 3.6μm, 3.8μm, 4μm, etc.

[0014] Specifically, in step S3, the repair material is one or a combination of boron oxide, boric acid, niobium oxide, indium oxide, aluminum oxide, and strontium oxide; the carbon source material is one or a combination of conductive carbon black, graphite powder, carbon nanotubes, and graphene.

[0015] Specifically, in step S3, the sintering temperature is 250°C-600°C, specifically 250°C, 300°C, 350°C, 400°C, 500°C, 600°C, etc.; the sintering time is 4h-8h, specifically 4h, 5h, 6h, 7h, 8h, etc.; the Li5 FeO 4 The Dv50 of the particles is 2.5 μm-4.5 μm, specifically 2.5 μm, 2.8 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, etc.

[0016] A high energy density additive material prepared by the preparation method of the high energy density additive material disclosed in the present invention, namely Li 5 FeO 4 Particles.

[0017] The invention discloses an application of a high energy density additive material in the preparation of a lithium ion battery.

[0018] The beneficial effects of the present invention are:

[0019] (1) The present invention first places a nano-sized iron salt in an organic solution system, utilizes organic matter to undergo polymerization reaction, forms an organic polymer coating layer on the surface of the nano-sized iron salt, obtains an organic polymer-coated precursor after solid-liquid separation and drying, and sinters the precursor and a lithium source under a protective atmosphere. During the sintering process, the organic matter on the surface of the precursor is converted into a dense carbon shell coating the surface of the particles at high temperature. The formed carbon shell can effectively inhibit the growth of the material particles, thereby effectively controlling the particle size of the finished particles, so that the prepared Li 5 FeO 4 The particle size is smaller and the particle size distribution is more uniform;

[0020] (2) After the material is crushed, the surface coating of the material will be damaged to a certain extent. In the present invention, after sintering and crushing in step S2, the obtained product is mixed with the repair substance and the carbon source substance and then sintered. After the repair substance and the carbon source substance are mixed with the material at a high speed and uniformly, the high temperature will cause the repair substance to melt. The molten repair substance enters the gaps on the surface of the product particles, thereby filling the damaged gaps, thereby achieving the effect of surface repairing the particles whose surface coating is damaged after the crushing operation, further improving Li 5 FeO 4 Granular material stability;

[0021] (3) The present invention can transform iron salts with low economic added value into high value-added, high energy density additive materials Li 5 FeO 4 Particles, and experiments have shown that the Li 5 FeO 4 The electrical properties, stability and specific capacity of the finished pellets are significantly better than those of materials prepared from conventional dry mixed carbon sources. The electrical capacity can reach more than 640 mAH / g, which is much higher than that of Li+ prepared from conventional dry mixed carbon sources. 5 FeO4 The granular material has a capacitance of 540 mAH / g. Moreover, the method disclosed in the present invention has a simple synthesis process, low processing cost and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Li synthesized in Example 1 5 FeO 4 SEM images of particles;

[0023] Figure 2 Li synthesized in Example 1 5 FeO 4 TEM images of particles;

[0024] Figure 3 Li synthesized in Experimental Example 1 5 FeO 4 The charge and discharge curve of

[0025] Figure 4 Li synthesized in Example 1, Example 2, and Comparative Example 1 5 FeO 4 The charge and discharge curves. DETAILED DESCRIPTION

[0026] The following is combined with Figure 1-4 The present invention is described in detail with specific embodiments. The embodiments shown below do not limit the invention described in the claims. In addition, the entire contents of the configurations shown in the following embodiments are not limited to the solutions required as the invention described in the claims.

[0027] A method for preparing an additive material with high energy density comprises the following steps:

[0028] S1: placing a nano-scale iron salt with a particle size of 100nm-900nm in an organic solution system, controlling and adjusting the solution temperature to 30℃-50℃, the solution pH to 3-6, and the stirring speed to 100rpm-400rpm, so that the organic substance undergoes a polymerization reaction, and then aging and standing for 2h-5h, performing solid-liquid separation and drying, the drying temperature is 70℃-150℃, and obtaining an organic polymer-coated precursor; the organic solution system is a mixture of one or more of resorcinol, formaldehyde, pyrrole, thiophene, aniline, and butyl titanate.

[0029] S2: Mix the organic polymer-coated precursor with a lithium source material so that the molar ratio of iron element to lithium element in the mixture is 1.0:(4.8-5.8), stir well, and then sinter and crush; the sintering temperature is 500℃-700℃, and the sintering time is 8h-30h; the crushing is carried out by a crusher, and the Dv50 of the material after crushing by the crusher is 2μm-4μm.

[0030] S3: Mix the crushed material, the repair material and the carbon source material and sinter them to obtain Li 5 FeO 4 The repair material is one or a combination of boron oxide, boric acid, niobium oxide, indium oxide, aluminum oxide, and strontium oxide, and the carbon source material is one or more of conductive carbon black, graphite powder, carbon nanotubes, and graphene. The sintering temperature is 250°C-600°C, and the sintering time is 4h-8h; the Li 5 FeO 4 The particle size Dv50 of the finished granules is 2.5μm-4.5μm.

[0031] The invention first places a nano-scale iron salt in an organic solution system, utilizes an organic substance to undergo a polymerization reaction, forms an organic coating layer on the surface of the nano-iron salt, obtains an organic polymer-coated precursor after solid-liquid separation and drying, and sinters the precursor and a lithium source under a protective atmosphere. During the sintering process, the organic substance on the surface of the precursor is converted into a dense carbon shell coated on the surface of the particle at a high temperature. The carbon shell can effectively inhibit the growth of the material particles, thereby effectively controlling the particle size of the finished product particles, so that the prepared Li 5 FeO 4 The particle size of the particles is smaller and the particle size distribution is more uniform; after sintering and crushing in step S2, the obtained product is mixed with a repair substance and a carbon source substance and then sintered, the purpose of which is to repair the surface of the particles whose surface coating layer is damaged after the crushing operation. After the repair substance and the carbon source substance are repaired and the secondary sintering, the surface damage caused by the crushing can be repaired, further improving the Li 5 FeO 4 The high energy density additive material Li prepared by the present invention has good stability. 5 FeO 4 The electrical properties, stability and specific capacity of the particles are significantly better than those of materials prepared from conventional dry mixed carbon sources. The electrical capacity can reach more than 640 mAH / g, which is much higher than that of Li+ prepared from conventional dry mixed carbon sources. 5 FeO 4 The granular material has a capacitance of 540 mAH / g. Moreover, the method disclosed in the present invention has a simple synthesis process, low processing cost and high efficiency.

[0032] Li prepared by the preparation method disclosed in the present invention 5 FeO 4 The particles can be used as additives in the preparation of lithium-ion batteries. 5 FeO 4 Particle lithium-ion batteries have the characteristics of high energy density and good stability.

[0033] Example 1

[0034] This example prepares a high energy density additive material, namely Li 5 FeO 4 Particles, see Figure 1 , the specific process is:

[0035] (1) Weigh 100 g of iron oxide with a particle size of 500 nm and place it in a reactor containing a mixed solution of resorcinol and formaldehyde, wherein the molar ratio of formaldehyde to resorcinol is 2:1. Stir the mixture thoroughly at a stirring speed of 200 rpm, and add a small amount of boric acid solution dropwise so that the pH value of the solution in the reaction system is 5.5. Heat the solution to 40°C, age it and allow it to stand for 3 hours. After 3 hours, filter press and dry it at a drying temperature of 80°C for 3 hours to obtain an organic polymer-coated precursor.

[0036] (2) The precursor obtained in the previous step is mixed with lithium hydroxide in a mixing device so that the molar ratio of lithium element to iron element in the mixture is 5.3:1.0. The mixing speed is 600 rpm and the mixing time is 30 min. The mixed materials are sintered in a nitrogen atmosphere at a sintering temperature of 650 °C and a sintering time of 15 h. The sintered materials are crushed by a crusher and their Dv50 is 2.7 μm.

[0037] (3) The obtained pulverized material is mixed with boron oxide and carbon nanotubes, wherein the amount of boron oxide added is 0.9% of the mass fraction of the pulverized material, and the amount of carbon nanotubes added is 0.2% of the mass fraction of the pulverized material. The mixing speed is 500 rpm and the mixing time is 20 min. The uniformly mixed material is sintered in a nitrogen atmosphere at a sintering temperature of 300 ° C and a sintering time of 6 h, thereby obtaining a high energy density additive material Li with good electrical performance and excellent stability. 5 FeO 4 Particles.

[0038] (4) Characterization test: Li obtained by this synthesis method 5 FeO 4 , the laser particle size analyzer was used for characterization test, and its Dv50 was 2.9μm, see Figure 2It can be seen that the particles formed have smaller surface and better uniformity. From the TEM image, it can be found that the coating effect of the material is better.

[0039] Example 2

[0040] This example prepares a high energy density additive material, namely Li 5 FeO 4 Particles, see Figure 1 , the specific process is:

[0041] (1) Weigh 100 g of iron oxide with a particle size of 500 nm, place it in a reaction kettle containing pyrrole solution, stir it thoroughly at a stirring speed of 200 rpm, and add a trace amount of boric acid solution dropwise so that the pH of the solution in the reaction system is 5.5, and heat the solution to 40° C., age it and let it stand for 3 hours, filter press it and dry it at a drying temperature of 80° C. for 3 hours to obtain an organic polymer-coated precursor.

[0042] (2) The precursor obtained in the previous step is mixed with lithium hydroxide in a mixing device so that the molar ratio of lithium element to iron element is 5.3:1.0, the mixing speed is 600 rpm, and the mixing time is 30 min. The mixed materials are sintered in a nitrogen atmosphere at a sintering temperature of 650°C and a sintering time of 15 h. The sintered materials are crushed by a crusher and their Dv50 is 2.7 μm.

[0043] (3) The obtained pulverized material was mixed with alumina and carbon nanotubes, wherein the amount of alumina added was 0.5% of the mass fraction of the pulverized material, and the amount of carbon nanotubes added was 0.2% of the mass fraction of the pulverized material, wherein the mixing speed was 500 rpm, the mixing time was 20 min, and the uniformly mixed material was sintered in a nitrogen atmosphere, the sintering temperature was 450° C., and the sintering time was 6 h. The laser particle size analyzer was used for characterization testing, and its Dv50 was 3.2 μm. The other properties were also similar to those of Example 1.

[0044] Comparative Example 1

[0045] This comparative example prepared a Li 5 FeO 4 Granular additive materials, the specific process is:

[0046] (1) Weigh 100 g of iron oxide with a particle size of 500 nm and mix it with lithium hydroxide, wherein the molar ratio of lithium to iron is 5.3:1.0. The mixing speed is 600 rpm and the mixing time is 30 min. The mixed materials are sintered in a nitrogen atmosphere at a sintering temperature of 650°C and a sintering time of 15 h. The sintered materials are crushed by a crusher and their Dv50 is 2.7 μm.

[0047] (2) The obtained pulverized material is mixed with boron oxide and carbon nanotubes, wherein the amount of boron oxide added is 0.9% of the mass fraction of the pulverized material, and the amount of carbon nanotubes added is 0.2% of the mass fraction of the pulverized material. The mixing speed is 500 rpm and the mixing time is 20 min. The mixed material is sintered in a nitrogen atmosphere at a sintering temperature of 300 and a sintering time of 6 h to obtain the additive material Li 5 FeO 4 .

[0048] Test Example 1

[0049] The Li prepared in Example 1 5 FeO 4 Weigh 30g of the material in a humidity environment of 15% and place it for 0h, 12h, 24h, 36h, and 48h, and mark it as A1, A2, A3, A4, and A5 respectively. To make button batteries from the materials of these five samples, it is necessary to go through the steps of slurry preparation, coating, drying, tableting, assembly, and cabinet testing: ① Prepare slurry, weigh 4g of material and mix it with conductive agent and binder, where the mass ratio of material: conductive agent: binder is 8:1:1, the binder used is PVDF, and the conductive agent is conductive carbon; ② Coating, use a scraper to coat on aluminum foil; ③ Drying, dry the coated electrode in a vacuum drying oven, the drying temperature is 120℃, and the drying time is 2h; ④ Tableting, use a roller machine to press the dried electrode; ⑤ Assemble the positive electrode, negative electrode, diaphragm, electrolyte and other battery parts into button batteries. The specific capacity was tested at a charging voltage of 4.25V and a charging rate of 0.1C.

[0050] Figure 3 Li synthesized in Example 1 5 FeO 4 The charge and discharge curves show that under the test conditions of 4.25V and 0.1C, the capacities of A1, A1, A2, A3, A4, and A5 are 652mAH / g, 657mAH / g, 651mAH / g, 646mAH / g, and 648mAH / g, respectively, indicating that the material has good electrical properties and stability.

[0051] Test Example 2

[0052] Li prepared in Example 1, Example 2, and Comparative Example 1 5 FeO 4Weigh 4g and mark them as B1, B2, and B3. To make button batteries from the materials of these five samples, the following steps are required: ① To prepare the slurry, weigh 4g of the material and mix it with the conductive agent and the binder. The mass ratio of the material: conductive agent: binder is 8:1:1. The binder used is PVDF and the conductive agent is conductive carbon. ② To coat, use a scraper to coat on aluminum foil. ③ To dry, dry the coated electrode in a vacuum drying oven at 120℃ for 2h. ④ To press, use a roller machine to press the dried electrode. ⑤ To assemble the positive electrode, negative electrode, separator, electrolyte and other battery parts into button batteries. The specific capacity is tested under the conditions of charging voltage 4.25V and charging rate 0.1C.

[0053] Figure 4 Li synthesized in Example 1, Example 2, and Comparative Example 1 5 FeO 4 The charge and discharge curves show that under the test conditions of 4.25V and 0.1C, the capacities of B1, B2 and B3 are 670mAH / g, 680mAH / g and 540mAH / g respectively, indicating that the material prepared by liquid phase coated polymer has better performance than the material prepared by conventional dry mixed carbon source.

[0054] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing an additive material with high energy density, characterized in that: The following steps are involved: S1: placing an iron salt in an organic solution system, stirring and controlling the temperature of the organic solution system to 30°C-50°C and the pH to 3-6, performing a polymerization reaction, aging and standing after the reaction, and then performing solid-liquid separation and drying to obtain an organic polymer-coated precursor; S2: mixing and stirring the organic polymer-coated precursor and the lithium source material, and then sintering and crushing to obtain a semi-finished product; S3: The crushed semi-finished product is mixed with a repair material and a carbon source material, and then sintered to obtain Li5FeO4 particles, i.e., a finished product of a high energy density additive material.

2. The method for preparing a high energy density additive material according to claim 1, characterized in that: In step S1, the particle size of the iron salt is 100nm-900nm; the organic solution system is a mixture of one or more of resorcinol, formaldehyde, pyrrole, thiophene, aniline, and butyl titanate.

3. The method for preparing a high energy density additive material according to claim 1, characterized in that: In step S1, the stirring speed is 100 rpm-400 rpm.

4. The method for preparing a high energy density additive material according to claim 1, characterized in that: In step S1, the aging standing time is 2h-5h; the drying temperature is 70℃-150℃.

5. The method for preparing a high energy density additive material according to claim 1, characterized in that: In step S2, the molar ratio of the iron element in the organic polymer-coated precursor to the lithium element in the lithium source material is 1.0:(4.8-5.8).

6. The method for preparing a high energy density additive material according to claim 1, characterized in that: In step S2, the sintering temperature is 500°C-700°C, and the sintering time is 8h-30h; the Dv50 of the semi-finished product obtained after the pulverization is 2μm-4μm.

7. The method for preparing a high energy density additive material according to claim 1, characterized in that: In step S3, the repair material is one or a combination of boron oxide, boric acid, niobium oxide, indium oxide, aluminum oxide, and strontium oxide; the carbon source material is one or a combination of conductive carbon black, graphite powder, carbon nanotubes, and graphene.

8. The method for preparing a high energy density additive material according to claim 1, characterized in that: In step S3, the sintering temperature is 250°C-600°C, and the sintering time is 4h-8h; the Dv50 of the Li5FeO4 particles obtained after the sintering is 2.5μm-4.5μm.

9. An additive material with high energy density prepared by the method according to any one of claims 1 to 8.

10. Use of the high energy density additive material according to claim 9 in the preparation of lithium ion batteries.

Citation Information

Patent Citations

  • Positive plate of high-energy-density lithium ion battery and preparation method of positive plate

    CN113764637A

  • Lithium supplement agent for positive electrode material of lithium battery and preparation method of lithium supplement agent

    CN115275200A